Study on the Aging Behavior of Two Acrylic Polyurethane Coatings under High and Low Temperature UV- Artificial Accelerated Aging Tests - PAN Dongyue, AN Jiangfeng, ZHOU Xuejie, PENG Feifan, CHEN Hao, CHEN Zhijian, WU Jun (Cailiao Baohu)
In order to investigate the aging behavior of acrylic polyurethane coatings in environments with high ultraviolet radiation intensity and large temperature differences， the aging processes of water-based and solvent-based acrylic polyurethane coatings were studied using UV-high and low-temperature artificial accelerated aging methods.Techniques such as super depth-of-field imaging， attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) and energy-dispersive spectroscopy (EDS) were employed to analyze the changes in microscopic morphology， molecular structure and elemental atomic fraction on the surfaces of the coatings.The performance changes and aging patterns of solvent-based and water-based coatings during the aging process were examined through electrochemical impedance spectroscopy (EIS)， water contact angle measurements， adhesion strength tests and glossiness assessments.Results showed that the water-based acrylic polyurethane coating system exhibited cracking， whereas the solvent-based coating system exhibited layering.Both coatings experienced significant reductions in glossiness， water contact angle and adhesion strength.The aging rate of the two coating systems initially increased rapidly and then slowed down， with an early appearance of the rate transition inflection point.Infrared spectroscopy analysis indicated that both coatings shared similar aging mechanisms， while EDS analysis demonstrated a faster aging rate for the water-based coating.Additionally， the weight of each performance index was calculated by entropy method， and the comprehensive aging grade under the test was obtained， which verified that the solventbased acrylic polyurethane coating system had relatively good weather resistance.